INNOVATIVE APPROACHES OVER SPORTS IN PRESENT ERA: AND STRATEGIES AND RESEARCH METHODS - Dr R Y Deshmukh (International Educational Journal of Science and Engineering, 2025)
Almost everyone has a smartphone, and physical education teachers can use such devices to their advantage to encourage their students to practice and exercise. Although they probably don’t like having students glued to their cell phones during class, the use of cell phones and phone apps should be encouraged if the educational benefits are obvious. There are many apps available, some for exercise tracking and nutritional support, while others help improve sports activities such as basketball. This improved the effectiveness of learning sports skills in theoretical and physical activities. Technology has the potential to facilitate more effective high school teaching and provide high school teachers with key information that can be used to influence their work. Teachers can also conduct video interviews to document student impressions of exercise and motor learning. The rapid development of electrical technology has had a major impact on the education systems of the world. Thanks to technology, especially mobile technology, physical education teachers now have a variety of tools to explore and improve their students’ physical skills. Focusing on vocational education contributes greatly to the overall development of children, and our hope is that students will be able to choose physical activity and sport as a vocational subject. It throws light on the entire education system in India as it is an ideal foundation for both primary and higher education.